La “belle” ou la Veuve : résistances, rébellions et tentatives d'évasion des condamnés à mort en France au XXe siècle - Nicolas Picard (Criminocorpus)
Prisoners who had been sentenced to death were subjected to a severe prison regime, a guarantee against suicide and escape. They were constantly under surveillance and didn’t have much room to act. Most of them could do nothing but wait for their fate, and the decision of pardon or execution. However, a few refused to resign themselves and rejected their situation in words and actions. They sometimes asserted their rights to benefit from better detention conditions. Escape or by default suicide, was always a hope. In spite of all the constraints, some rare convicts succeeded in leaving their cells, even if they seldom managed to stay long on the run.